Cover Feature: Designed Complex Peptide‐Based Adaptive Systems: A Bottom‐Up Approach (ChemSystemsChem 1/2023). Issue 1 (21st December 2022) - Kassem, Salma; Ulijn, Rein V.
Abstract : The Cover Feature shows a network of interacting peptide components that illustrates complex peptide‐based systems. System complexity is built from the bottom‐up through self‐organization and functional reconfiguration of interacting and inter‐converting peptide sequences. Cover design by Ella Maru Studio. More information can be found in the Review by Salma Kassem and Rein V. Ulijn .